2015
DOI: 10.1021/acs.jpcb.5b05681
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Interdomain Interactions on RfaH Dynamics and Conformational Transformation

Abstract: The transcription antiterminator RfaH has been shown to undergo major structural rearrangements to perform multiple functions. Structural determination of the C-terminal domain (CTD) of RfaH showed that it can exist as either an α-helix bundle when interfacing with the N-terminal domain (NTD) or as a β-barrel conformation when it is not interfacing with the NTD. In this paper, we investigate the full RfaH with both CTD and NTD using a variety of all-atom molecular dynamics (MD) simulation techniques, including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
42
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(49 citation statements)
references
References 56 publications
7
42
0
Order By: Relevance
“…VP40 exists in various conformations depending on the required function: a butterfly shaped dimer is involved in the transport of the protein to a membrane, a hexamer to form the viral matrix, and an octamer ring structure to bind to RNA and regulate viral transcription . As with other recently identified transformer proteins such as the RfaH transcription factor, the structural basis and mechanisms of large‐scale structural transformation in VP40 are not well understood.…”
Section: Introductionmentioning
confidence: 99%
“…VP40 exists in various conformations depending on the required function: a butterfly shaped dimer is involved in the transport of the protein to a membrane, a hexamer to form the viral matrix, and an octamer ring structure to bind to RNA and regulate viral transcription . As with other recently identified transformer proteins such as the RfaH transcription factor, the structural basis and mechanisms of large‐scale structural transformation in VP40 are not well understood.…”
Section: Introductionmentioning
confidence: 99%
“…Since the trigger for RfaH metamorphosis is the complete ops-paused TEC (13,14,16), it is challenging to study this process experimentally. Instead, most of the thermodynamic and kinetic studies have used computational approaches to directly explore this fold-switch by simulating either the isolated CTD (18)(19)(20) or the entire RfaH protein (21,22). Although the RfaH CTD is composed of only 51 residues (residues 112-162), its transition from alpha to beta has not been observed through conventional molecular dynamics (19), but through the use of enhanced sampling techniques (18,20,22) or reduced system granularity (21,23).…”
Section: Introductionmentioning
confidence: 99%
“…Instead, most of the thermodynamic and kinetic studies have used computational approaches to directly explore this fold-switch by simulating either the isolated CTD (18)(19)(20) or the entire RfaH protein (21,22). Although the RfaH CTD is composed of only 51 residues (residues 112-162), its transition from alpha to beta has not been observed through conventional molecular dynamics (19), but through the use of enhanced sampling techniques (18,20,22) or reduced system granularity (21,23). A way to circumvent such computing barriers is the use of confinement simulations, which rely on a discontinuous thermodynamic integration to estimate the absolute free energy of a clearly defined energy well (24).…”
Section: Introductionmentioning
confidence: 99%
“…4 VP40 is involved in multiple functions during the viral life-cycle 5 and protein multifunctionality often requires proteins to undergo conformational changes. 68 It has been shown that, depending on the function, EBOV VP40 (eVP40) exists in different conformations such as a butterfly shaped dimer involved in the transport of the protein to the membrane, a hexamer to form the viral matrix beneath the lipid-envelope, and an octamer ring structure to bind RNA and regulate viral transcription. 5 The X-ray crystal structure determination of the dimeric, hexameric and octameric forms of eVP40 has provided a great deal of information about the structural transformation of the protein into various oligomeric states for performing different functions.…”
Section: Introductionmentioning
confidence: 99%